2020
DOI: 10.1038/s41467-020-18617-z
|View full text |Cite|
|
Sign up to set email alerts
|

Bone morphogenetic protein 7 promotes resistance to immunotherapy

Abstract: Immunotherapies revolutionized cancer treatment by harnessing the immune system to target cancer cells. However, most patients are resistant to immunotherapies and the mechanisms underlying this resistant is still poorly understood. Here, we report that overexpression of BMP7, a member of the TGFB superfamily, represents a mechanism for resistance to anti-PD1 therapy in preclinical models and in patients with disease progression while on immunotherapies. BMP7 secreted by tumor cells acts on macrophages and CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 70 publications
(93 reference statements)
0
39
0
1
Order By: Relevance
“…Of these, 15 genes ( IGHJ3 , IGLV6-57 , TNFRSF17 , IGLV2-18 , IGHD3-22 , IGHV3-64 , IL2RG , IGHJ1 , IGLV4-60 , IGLV5-48 , IGLC7 , IGHA2 , IL33 , GKN1 , CCL25 ) were upregulated and only 1 gene ( BMP7 ) were downregulated in the Immunity_H group. BMP7 , bone morphogenetic protein 7, can regulate immune cell responses and are immunosuppressive in cancer, which can act as a potential immunotherapeutic target ( 29 ). The log2 fold change values in the DEGs, DEIGs, PIGs, and their FDR values in both Immunity_H and Immunity_L groups were shown in Figure 3D .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 15 genes ( IGHJ3 , IGLV6-57 , TNFRSF17 , IGLV2-18 , IGHD3-22 , IGHV3-64 , IL2RG , IGHJ1 , IGLV4-60 , IGLV5-48 , IGLC7 , IGHA2 , IL33 , GKN1 , CCL25 ) were upregulated and only 1 gene ( BMP7 ) were downregulated in the Immunity_H group. BMP7 , bone morphogenetic protein 7, can regulate immune cell responses and are immunosuppressive in cancer, which can act as a potential immunotherapeutic target ( 29 ). The log2 fold change values in the DEGs, DEIGs, PIGs, and their FDR values in both Immunity_H and Immunity_L groups were shown in Figure 3D .…”
Section: Resultsmentioning
confidence: 99%
“…CCL25 (chemotactic cytokines 25) can promote the proliferation by activating the AKT signaling and intratumoral delivery of CCL25 may enhance immunotherapy ( 37 ). BMP7 , a member of the TGFB superfamily, inhibits the MAPK14 signaling pathway and induces resistance to anti-PD1 therapy ( 29 ). Gastrokine 1 ( GKN1 ) has been found to suppress GC cell growth by activating the p16/Rb pathway ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…et al found that BMP7 impairs proinflammatory responses in the tumor microenvironment by inhibiting mitogen-activated protein kinase 14 (MAPK14) expression in macrophages and CD4 + T cells. Knockdown of BMP7 in combination with anti-PD1 activates CD4 + and CD8 + T cells in tumors, decreases M2 macrophages, and resensitizes resistant tumors to immunotherapies [ 48 ]. Emerging evidence demonstrates that targeting epigenetic elements that promote tumor progression and inhibit immune cell activity can enhance antitumor immunity by reshaping the TME.…”
Section: Strategies Overcoming Immunotherapy Resistancementioning
confidence: 99%
“…identified two immune subtypes of triple-negative breast cancer, including neutrophil-enriched (NES) and macrophage-enriched subtypes (MES), and the MES-to-NES conversion can mediate acquired ICBs resistance ( 100 ). Furthermore, tumor-derived bone morphogenetic protein 7 (BMP7), a member of the TGF-β superfamily, promotes resistance to immunotherapy ( 101 ). Adenosine is considered an important immunosuppressive cytokine ( 102 ).…”
Section: Underlying Mechanisms Of Armentioning
confidence: 99%